Sarah Huxtable-Mohr, "Islamic Liberation Psychology: The Transformational Force of Self-Development, Community Empowerment, and Revolutionary Change" (2025) - Jelinic, Ana Borges (Journal for the academic study of religion, 2025)
Sarah Huxtable-Mohr, Islamic Liberation Psychology: The Transformational Force of Self-Development, Community Empowerment, and Revolutionary Change, London: Routledge, 2025, pp. 176, $71.19, ISBN 9781032625003 (pbk).